Effects of high-intensity interval training on increase in peak oxygen consumption after stroke: systematic review (Research, Society and Development, 2023)
The study is a systematic review with the objective of evaluating the effects of High Intensity Interval Training (TIAI) on the increase in peak oxygen consumption (VO2peak) after stroke. The search was carried out in the MEDLINE electronic databases through the BVS database, in PubMed, SciELO, Lilacs and in the Cochrane Library database through the following terms indexed in DeCS and MeSH in English “Stroke”, “High Intensity Interval Training” and “Oxygen Consumption”. Studies available in full, without restriction. There was no restriction regarding ethnicity, age or gender. Duplicate, incomplete studies, those that did not measure the VO2peak before and after the intervention or partially presented data were excluded. A total of 3473 studies were found, of which only seven were included. All studies obtained an increase in VO2peak after TIAI sessions as a result. The increase in the participants' VO2peak occurred after training sessions lasting around 30 to 40 minutes, with average intervals of 30 seconds. It is concluded that TIAI can be an effective strategy to improve the cardiorespiratory fitness of people who have suffered a stroke by increasing VO2peak.